Validating the short measure of the Effort-Reward Imbalance Questionnaire in older workers in the context of New Zealand - Li, Jian; Herr, Raphael (Journal of occupational health and epidemiology, 2017)
Objectives: The objective of this study was to validate a short version of the Effort-Reward-Imbalance (ERI) questionnaire in the context of New Zealand among older full-time and part-time employees. Methods: Data were collected from 1694 adults aged 48-83 years (mean 60 years, 53% female) who reported being in full- or part-time paid employment in the 2010 wave of the New Zealand Health, Work and Retirement study. Scale reliability was evaluated by item-total correlations and Cronbach's alpha. Factorial validity was assessed using multi-group confirmatory factor analyses assessing nested models of configural, metric, scalar and strict invariance across full- and part-time employment groups. Logistic regressions estimated associations of effort-reward ratio and over-commitment with poor physical/mental health, and depressive symptoms. Results: Internal consistency of ERI scales was high across employment groups: effort 0.78-0.76; reward 0.81-0.77, and over-commitment 0.83-0.80. The three-factor model displayed acceptable fit in the overall sample (X2/df = 10.31; CFI = 0.95; TLI = 0.94; RMSEA = 0.075), and decrements in model fit indices provided evidence for strict invariance of the three-factor ERI model across full-time and part-time employment groups. High effort-reward ratio scores were consistently associated with poor mental health and depressive symptoms for both employment groups. High over-commitment was associated with poor mental health and depressive symptoms in both groups and also with poor physical health in the full-time employment group. Conclusions: The short ERI questionnaire appears to be a valid instrument to assess adverse psychosocial work characteristics in old full-time and part-time employees in New Zealand.